Efektivitas Media Pembelajaran Berbasis Teknologi untuk Siswa SDN Kunciran 3 - Ahmad Budi Trisnawan Wawan (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2025)
This study aims to analyze the effectiveness of technology-based learning media in improving the quality of the teaching and learning process and student learning outcomes at SDN Kunciran 3. In the context of 21st-century education, integrating technology into learning activities is a necessity for creating an interactive, enjoyable, and relevant learning environment. The research method used is a quantitative method with a quasi-experimental approach, involving two groups of fifth-grade students: an experimental group that uses technology-based learning media such as interactive videos, educational applications, and digital quizzes; and a control group that uses conventional methods in the form of lectures and textbooks. Data were collected through pre-tests and post-tests to measure improvements in learning outcomes, as well as questionnaires to assess student motivation and responses to the learning media used. The results showed that students in the experimental group experienced a significant increase in learning outcomes compared to the control group, with an increase in learning motivation that was also higher. This study concludes that the use of technology-based learning media has a positive impact on learning effectiveness, especially in improving understanding of the material, active student involvement, and interest in learning. Therefore, technology integration in learning at the elementary school level is highly recommended to support a more modern and adaptive educational transformation.